Fatigue lifetime prediction of a reduced-diameter dental implant system: Numerical and experimental study. Issue 9 (September 2018) - Duan, Yuanyuan; Gonzalez, Jorge A.; Kulkarni, Pratim A.; Nagy, William W.; Griggs, Jason A.
Highlights: Finite element modeling and accelerated lifetime testing yielded similar predictions. Fractographic examination of failure origin agreed with finite element predictions. Fatigue lifetime was predicted to be dependent on the stiffness of holder material. Abstract: Objective: To validate the fatigue lifetime of a reduced-diameter dental implant system predicted by three-dimensional finite element analysis (FEA) by testing physical implant specimens using an accelerated lifetime testing (ALT) strategy with the apparatus specified by ISO 14801. Methods: A commercially-available reduced-diameter titanium dental implant system (Straumann Standard Plus NN) was digitized using a micro-CT scanner. Axial slices were processed using an interactive medical image processing software (Mimics) to create 3D models. FEA analysis was performed in ABAQUS, and fatigue lifetime was predicted using fe-safe ® software. The same implant specimens (n = 15) were tested at a frequency of 2 Hz on load frames using apparatus specified by ISO 14801 and ALT. Multiple step-stress load profiles with various aggressiveness were used to improve testing efficiency. Fatigue lifetime statistics of physical specimens were estimated in a reliability analysis software (ALTA PRO). Fractured specimens were examined using SEM with fractographic technique to determine the failure mode. Results: FEA predicted lifetime was within the 95% confidence interval of lifetime estimated by experimental results, which suggested that FEA prediction was accurate for this implant system. The highest probability of failure was located at the root of the implant body screw thread adjacent to the simulated bone level, which also agreed with the failure origin in physical specimens. Significance: Fatigue lifetime predictions based on finite element modeling could yield similar results in lieu of physical testing, allowing the use of virtual testing in the early stages of future research projects on implant fatigue.